Structural and optical properties o plasma-deposited a-C:H:Si:O:N films - Lopes, Juliana Feletto Silveira Costa [UNESP] (2021)
Thin a-C:H:Si:O:N films were deposited from plasmas fed hexamethyldisiloxane, oxygen and nitrogen, and characterized as a function of the partial pressure of oxygen in the feed, Rox. Deposition rates varied from 10 to 27 nm min-1. Surface roughness was independent of Rox, being around 10 nm. The films contain C=C and C=O, and also Si-C and Si-O-Si groups. Lower [C] and [N] but greater [O] and [Si] were measured in the films as Rox was increased. Refractive indices of ~ 1.5 and optical energy gaps which fell from ~ 3.3 to ~2.3 eV were observed with increasing Rox. The Urbach energy fell with increasing optical gap, which is characteristic of amorphous materials. Such materials have potential as transparent barrier coatings.